La nulidad de una sentencia no ejecutada cuando el actor no ha sido parte procesal. En el juicio civil - Ortega Caicedo, Ita Maria (2014)
This thesis refers to "THE REVOCATION OF SENTENCE NOT DONE WHEN THE ACTOR HAS NOT BEEN A PARTY LITIGATION. IN CIVIL” JUDGMENT, Art 297 of the Code of Civil Procedure mandates that: "The final judgment takes irrevocable effects on the parties that followed the trial or their successors in right. Consequently, you can not follow new trial when the two judgments any both subjective identity, constituted by the intervention of the same parts as objective identity, which is that it demands the same thing, quantity or made, based on the same cause, reason or right. To appreciate the scope of the judgment will take into account not only the operative part, but also the basis of the same objectives. " The Code of Civil Procedure mandates that can only demand the annulment of a judgment which has been defeated at trial, ie who has been party to the proceedings, but in professional life there are many decisions that seriously affect others, but procedurally no may bring an action for nullity because it was not part of the trial proceedings which judgment is needed to sue. Article 69, paragraph 3 of the Constitution of Republic of Ecuador mandates that "The State shall guarantee equal rights in decision-making for the administration of the conjugal partnership and real society"; because the Constitution guarantees to property as a constitutional right, a progressive right for people; this means that a process the litigants in a trial division of property, make a partition of goods for only them, then once the judgment is it that other people have the right to partition the property, in this if there are more siblings, it would affect and violate the right to sue the invalidity of the judgment because it was not part of the trial proceedings.